To Merge or Not to Merge: Observations and Recommendations - Gary L Vacin (Journal of Applied Communications, 1991)
Water Resources Research Institutes (WWRIs) have traditionally targeted technical audiences with information transfer efforts, but non-technical audiences also play a role in decision-making.